IMPLEMENTASI KEBIJAKAN PENANGGULANGAN HIV/AIDS DI BADAN LAYANAN UMUM DAERAH PUSKESMAS PARONGPONG - Akbari, Muhamad Ali; Suhermanudin, Suhermanudin (Ilmu Pemerintahan Universitas Langlangbuana, 2023)
The background to this research is that the implementation of the HIV/AIDS Management Policy at the Parongpong Community Health Center Regional Public Service Agency, Parongpong District, has not been optimal. Based on these problems, the researcher formulated an identification problem on how to implement the HIV/AIDS prevention policy at the Parongpong Community Health Center Regional Public Service Agency, Parongpong District. The purpose of this research is to find out and analyze in more depth how the HIV/AIDS Management Policy is implemented at the Regional Public Service Agency (BLUD) Parongpong Health Center, Parongpong District. By analyzing this research problem, the Policy Implementation theoretical approach according to Edward III in Subarsono is used, which consists of 4 dimensions, namely Communication, Resources, Disposition, Bureaucratic Structure. The method used in this research is a descriptive method with a qualitative approach with data sources obtained through primary and secondary sources. Data collection techniques using in-depth interviews, observation and documentation. Based on the results of the analysis and data validity tests carried out and research results obtained which show that the implementation of the HIV/AIDS Management Policy at the BLUD Parongpong Community Health Center, Parongpong District, is not in accordance with the HIV/AIDS Management Policy at the Parongpong Community Health Center BLUD, Parongpong District, such as, lack of socialization, lack of expert staff/ Human Resources.